The Knowledge Backflash / Can we Manage Know-How, or is it All in the Mind? The Warnings Begin - Macvicar Stephen; Tate Paul (1998)
The Cyber-Picket Line, Why the Giants Won't Survive, Service Without a Smile, Buying an Online Strategy, Information Democracy, A Question of Priorities, The Bottom Line on Knowledge, Comment, Strategy Watch, Facts and Forecasts, The IS Network, End Page.